CEEPUS: Active Methods in Setting up a New Regional Academic Exchange Program - Sorantin Elisabeth (De Gruyter, 2020)
CEEPUS - Central European Exchange Program for University Studies - is the biggest regional academic exchange program in Europe, currently comprising 15 countries. CEEPUS awards mobility grants to students and teachers, mostly in the framework of networks. From a much-doubted bold experiment, CEEPUS has evolved into a best practice example and has more than fulfilled its original expectations. As CEEPUS III is to expire on April 30, 2025, the discussion is on whether and in which form a possible CEEPUS IV shall be developed.